Bosnian study of APOE distribution (BOSAD): a comparison with other European populations - Grażyna Adler; Mateusz A. Adler; Anna Urbańska; Karolina Skonieczna-Żydecka; Emina Kiseljakovic; Amina Valjevac; Miłosz Parczewski; Almira Hadzovic-Dzuvo (Taylor & Francis Group, 2017)
Background: The ε2, ε3 and ε4 alleles of APOE gene have been associated with several diseases in different populations. Data on the frequency of alleles are used in both a clinical and evolutionary context. Although the data on frequency of these alleles are numerous, there are no reports for the population of Bosnia and Herzegovina. Aim: To estimate the frequency of APOE alleles in a healthy Bosnian population and compare it to data for other European populations. Subjects and Methods: Overall, 170 unrelated Bosnian subjects (108 female and 62 male), aged 53.0 (±5.0) years were included in this study. Genotypes were determined by real-time PCR. Results: In our group the prevalence of heterozygotes E2/E3, E2/E4 and E3/E4 was 20.6%, 3.5% and 12.9%, respectively, while the prevalence of homozygotes E2/E2, E3/E3, E4/E4 was 0.6%, 61.2% and 1.2%, respectively, with a mean frequency of ε2, ε3 and ε4 alleles of 12.6%, 78.0% and 9.4%, respectively. Conclusions: In studied European populations we observed a linear, gradually increasing trend in the frequency of ε4 allele from South to North (Pearson's test 0,7656, p value <0.00001), and the Bosnian population fits into this pattern perfectly.